2019
DOI: 10.1007/s40258-019-00498-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a School-Based Social and Emotional Learning Intervention: Evidence from a Cluster-Randomised Controlled Trial of the Promoting Alternative Thinking Strategies Curriculum

Abstract: Background School-based social and emotional learning interventions can improve wellbeing and educational attainment in childhood. However, there is no evidence on their effects on health-related quality of life (HRQoL) or on their cost effectiveness. Objective Our objective was to evaluate the cost effectiveness of the Promoting Alternative Thinking Strategies (PATHS) curriculum. Methods A prospective economic evaluation was conducted alongside a cluster-randomised controlled trial of the PATHS curriculum imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Different MCDA methods are used to aid the decision-making process in many branches of knowledge, each one with its particularity [30,31]. To perform an ICER, the difference of total cost and total effectiveness between two treatments must be computed to reach an incremental cost and an incremental effectiveness [32]. Thus, the use of an MCDA method that performs a pairwise comparison between treatments' performances difference, criterion per criterion, can be a way to complement CEA due to the similarity of these methodologies.…”
Section: Mcda Methodsmentioning
confidence: 99%
“…Different MCDA methods are used to aid the decision-making process in many branches of knowledge, each one with its particularity [30,31]. To perform an ICER, the difference of total cost and total effectiveness between two treatments must be computed to reach an incremental cost and an incremental effectiveness [32]. Thus, the use of an MCDA method that performs a pairwise comparison between treatments' performances difference, criterion per criterion, can be a way to complement CEA due to the similarity of these methodologies.…”
Section: Mcda Methodsmentioning
confidence: 99%
“…Therefore, a cost-consequence framework that tabulates costs against several outcomes for staff and students is appropriate, rather than a more reductive cost-effectiveness or cost-utility analysis that attempts to summarise efficiency in a single ratio. 77 It provides a more complete analysis for policy-makers than a 'cost per unit improvement in WEMWBS score', which has no easy interpretation. Previous research has demonstrated limited correlation and overlap between the WEMWBS well-being scores and health-related utility scores (such as the EuroQol-5 Dimensions, three-level version) used to estimate quality-adjusted life-years.…”
Section: Cost-consequence Analysismentioning
confidence: 99%
“…Several articles focused on efforts to improve mental health care for vulnerable populations [15][16][17][18]. Cullinan et al examined socioeconomic disparities in unmet need for student mental health services in higher education in Ireland [15].…”
mentioning
confidence: 99%
“…Turner et al undertook an economic evaluation of a school-based social and emotional learning Intervention in the United Kingdom [18]. The intervention, Promoting Alternative Thinking Strategies (PATHS), aim of to promote self-control, emotional understanding, positive selfesteem, relationships and interpersonal problem-solving skills among children in pre-school and primary education settings through the provision of a taught curriculum.…”
mentioning
confidence: 99%
See 1 more Smart Citation